2012
DOI: 10.1007/s00221-012-3110-z
|View full text |Cite
|
Sign up to set email alerts
|

The cost of moving with the left hand

Abstract: Precise left-hand movements take longer than right-hand movements (for right-handers). To quantify how left-hand movements are affected by task difficulty and phase of movement control, we manipulated the difficulty of repetitive speeded aiming movements while participants used the left or right hand. We observed left-hand costs in both initial impulse and current control phases of movement. While left-hand cost during the initial impulse phase was small, left-hand cost during the current control phase varied … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
6
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 41 publications
2
6
0
Order By: Relevance
“…The data in Experiment 3 reassured us that the kinds of movements studied here were indeed easier for the right hand than for the left, replicating previously reported right-versus-left hand differences in movement times (Flowers, 1975;Vaughan et al, 2012). However, we also found a larger effect of hand orientation.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The data in Experiment 3 reassured us that the kinds of movements studied here were indeed easier for the right hand than for the left, replicating previously reported right-versus-left hand differences in movement times (Flowers, 1975;Vaughan et al, 2012). However, we also found a larger effect of hand orientation.…”
Section: Discussionsupporting
confidence: 92%
“…We expected differences between the left and right hands in this task because it has been shown that in right-handed participants, the right hand performs aiming movements more quickly than does the left hand (Flowers, 1975; Vaughan, Barany, & Rios, 2012). We also expected longer movement times for thumb-down moves than for thumb-up moves.…”
Section: Methodsmentioning
confidence: 99%
“…Regarding the preferred and non-preferred hand performances, our results also agree with prior research by Woodworth [2], todor and doane [30], and Vaughan et al [16], by verifying greater precision and speed for the preferred hand on similar ids. Although task parameters slightly varied between hands, hampering between-hand comparisons, there was a clear performance superiority with the preferred hand (more St and faster Mt).…”
Section: Human Movementsupporting
confidence: 92%
“…Within this scenario, handedness is an essential factor that affects motor responses [15], as each hand can be considered as a different effector within the same individual, which interacts differently with the constraints imposed by a given motor task. For instance, Vaughan et al [16] analysed the impact of handedness during alternated discrete touching with a stylus in 2 side-by-side targets, aiming to perform as many touches as possible while still being accurate. these authors verified that responses with the preferred right hand were faster and more accurate, occurring in shorter movement time for tasks of similar difficulty, just as Woodworth [2] had presented long ago.…”
Section: Introductionmentioning
confidence: 99%
“…That is, neurocognitive representations of objects should differ between individuals whose bodies cause them to interact with the objects in predictably different ways (e.g., between individuals with right- vs. left-hand dominance). Action execution with the non-dominant hand in the context of complex tasks has been associated with reliable performance costs in movement speed (Grosskopf & Kuhtz-Buschbeck, 2005; Vaughan, Barany, & Rios, 2012). Additionally, handedness has been shown to influence perception of object size, with graspable items placed in the dominant hand being judged as smaller than items placed in the non-dominant hand, even when apparent hand size is artificially manipulated (Linkenauger, Witt, & Proffitt, 2011).…”
Section: Effects Of Body-specific Experience On Object Knowledge Retrmentioning
confidence: 99%